Simplify \(\frac{3(2^{n+1}) - 4(2^{n-1})}{2^{n+1} - 2^n}\...
Simplify 3(2n+1)−4(2n−1)2n+1−2n
2n+1
2n-1
4
1/4
Correct answer is C
Start by expanding 3(2n+1)−4(2n−1)2n+1−2n:
3×2n×21−22×2n×2−12n×2−2n
NUMERATOR : 2n ( 31 X 21 - 22 X 2−1 )
--> 2n ( 3 X 2 — 4 X 12 )
--> 2n ( 6 - 2 )
--> 2n (4)
DENOMINATOR : 2n ( 21 - 1 )
--> 2n ( 2 - 1)
--> 2n
: [ 2n ( 4) ] ÷ 2n
= 4
If y = 3 sin(-4x), dy/dx is ...
If a positive integer, list the values of x which satisfy the equation 3x - 4 < 6 and x - 1 > 0...
Find the midpoint of the line joining P(-3, 5) and Q(5, -3). ...
In the diagram O is the center of the circle. Reflex angle XOY = 210° and the length of the mino...
Given that p=1+√2 and q=1−√2, evaluate p2−q22pq. ...
Solve the equation 3 + 5x - 2x2 = 0...
Solve the equation: 13x + 25 = 34x - 16...
Two binary operations ∗ and ⊕ are defined as m ∗ n = mn - n - 1 and m \(\oplu...